2021
DOI: 10.4136/ambi-agua.2630
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water quality indices: a systematic review

Abstract: This analysis applied systematic review as a methodology for identifying, analyzing and interpreting data on the use of water quality indices for human consumption. Scientific articles were searched in the “PubMed”, “Scielo”, “ScienceDirect” and “Web of Science" databases, using the keywords “drinking water” and “water quality index”, with a custom interval between 2000 and 2020. The results indicated 82,573 published articles, with 16 of them being selected after a filtering process. The occurrence of 11 wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The pH values were within the acidic range with mean values below permissible pH limits (6.5 to 9) for aquaculture (Ekubo and Abowei2011;Bhatnagar and Devi, 2019). The mean values exceeded also the range for water drinking, swimming/bathing and agriculture purpose (Klamt et al, 2021).…”
Section: Water Ph and Dissolved Oxygenmentioning
confidence: 80%
“…The pH values were within the acidic range with mean values below permissible pH limits (6.5 to 9) for aquaculture (Ekubo and Abowei2011;Bhatnagar and Devi, 2019). The mean values exceeded also the range for water drinking, swimming/bathing and agriculture purpose (Klamt et al, 2021).…”
Section: Water Ph and Dissolved Oxygenmentioning
confidence: 80%
“…The National Sanitation Foundation Water Quality Index (NSFWQI) is one of the most widely used methods (Abbasi & Abbasi, 2012;Klamt et al, 2021;Ott, 1978;Uddin et al, 2021), although the choice of WQI model is often determined by the intended use of the water source to be assessed, the availability of suitable water quality data, and site or region of use (Akhtar et al, 2021;Kachroud et al, 2019;Lumb et al, 2011). Other commonly used models in North America which have also been modified for application in other parts of the world include Brown et al 1972 Water Quality Index (BWQI) (Brown et al, 1973), Oregon Water Quality Index (Brown, 2016), and the Canadian Council of Ministers of the Environment Water Quality Index.…”
Section: Core Ideasmentioning
confidence: 99%
“…Despite WQI's status as a nonregulatory measurement (Akkoyunlu & Akiner, 2012; USF Water Institute, 2022), it is widely used because it helps the public and policymakers better understand critical water quality information. Further, it aids regulatory authorities in water quality valuation such as quantification and monetization, useful for watershed management (Akkoyunlu & Akiner, 2012; Davies, 2006; Debels et al., 2005; Klamt et al., 2021; Walsh & Wheeler, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Access to water services and water quality are different among countries, being less improved in low- or middle-income countries with large rural areas due to the low monitoring capacity [ 7 , 8 ]. Thus, data regarding water quality are scarce or absent in those contexts, increasing the health risks due to unknown water conditions [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review identified, analyzed, and interpreted more than 11 water quality indexes for human consumption, including pH, nitrate, turbidity, chloride, and sulfate [ 7 ]. Microbiological contamination, chemical contaminants, health aspects, and the acceptability of consumers are concerns related to water quality in developing countries [ 2 ].…”
Section: Introductionmentioning
confidence: 99%